The determinants of household debts in Malaysia during the period of: Q3 2009 to Q4 2016 / Muhamad Hateem Khan Ayob Khan - Ayob Khan, Muhamad Hateem Khan (Faculty of Business and Management, 2017)
The purpose of this study is to investigate the determinants of household debts in Malaysia during the period of Q3 2009 to Q4 2016. The study use descriptive statistics and ordinary least squared method with normality, serial correlation, heteroscedasticity, multicollinearity test and model specification. The findings of this study show that only two independent variables are significant while the other one is insignificant. Basically this research study based on the previous study Increasing Household Debts and its Relation to GDP, interest rate and House Price: Malaysia’s perspective by Sharezan Rahman and Mansur Masih (2014).